Stonehenge : is the medium the message? - Barrett, John C.
In June ANTIQUITY published a novel contribution by Mike Parker Pearson and his Madagascan colleague Ramilisonina, which addressed the question of the significance of stone at Stonehenge(ANTIQUITY 72: 308Ð76). They argued that stone symbolized death and the dead, and provided examples from ethnographic studies to support this notion. The paper has stimulated two repliesÐfrom John Barrett & Kathryn Fewster, and from Alasdair Whittle. We are pleased to publish these here, as part of the continuing debate on analogy in archaeology, and on Stonehenge.